Paneldebatt - Panel discussion - Rahola and others, Tua (Rangifer, 1986)
Participantsof the panel: Tua Rahola, Finland, Kalevi Salminen, Finland, Torolf Berthelsen, Norge, Atle Ørbeck-Sørheim, Norge, Bernt Jones, Sverige, Eland Pääjärvi, Sverige, Jan-Olof Snihs, Sverige. Leader of the discussion: Bengt Westerling